Role of magnetic resonance spectroscopy, diffusion-weighted imaging, and apparent diffusion coefficient in distinguishing intracranial space-occupying lesions. (Student's Journal of Health Research Africa, 2026)
Introduction Objectives: To evaluate the role of magnetic resonance spectroscopy (MRS), diffusion-weighted imaging (DWI), and apparent diffusion coefficient (ADC) mapping in distinguishing infective from neoplastic intracranial space-occupying lesions (ICSOLs).MethodsThis prospective observational study was conducted at a tertiary care teaching hospital over two years. Eighty patients presenting with seizures, headache, neurological deficits, or an intracranial space-occupying lesion detected on computed tomography underwent multiparametric MRI, including conventional MRI, DWI, ADC mapping, and MRS. Imaging findings were correlated with histopathological diagnoses. Statistical analyses were performed using appropriate parametric and non-parametric tests, with a p-value
Keywords: Magnetic Resonance Spectroscopy; Diffusion-Weighted Imaging; Apparent Diffusion Coefficient; Intracranial Space-Occupying Lesions; Glioblastoma